Upaya Guru PKn dalam Membentuk Nilai Moral Siswa di SMP Negeri 37 Halmahera Selatan - Abdullah Ishak; Subhan Hayun (Jurnal Geocivic, 2020)
The low quality of human resources is a fundamental problem that can hinder national economic development and development. Structuring human resources needs to be pursued gradually and continuously through a quality education system both in the formal, informal, and non-formal education pathways, from basic education to higher education. In accordance with observations/observations of researchers in the field, especially in one of the institutions (schools) of SMP Negeri 37 Halmahera Selatan. Decadence/deterioration of moral values occurs, such as Students no longer develop and preserve the moral values of Pancasila. They are universally dynamic and open. The cultivation of moral values in schools is currently experiencing a setback. Thus Civics teachers seek to find alternatives in order to shape the moral values of SMP Negeri 37 Halmahera Selatan students. This study uses descriptive qualitative methods and aims to determine the efforts made by Civics teachers in shaping the moral values of students of SMP Negeri 37 Halmahera Selatan. And want to know the factors inhibiting the moral value of students of SMP Negeri 37 Halmahera Selatan. The results of this study indicate that Civics teachers have an effort to form good moral values of students, do not interrupt other people's conversations, respect teachers and parents at home. Meanwhile, the inhibiting factor for Civics teachers in shaping the moral values of students of SMP Negeri 37 Halmahera Selatan is dealing with students who have a tendency to be lazy, spoiled, and students often skip school.